Responding to the pressing yet unrecognized needs of student-parents amid the COVID-19 pandemic. Issue 8 (17th November 2022) - Lin, Hung-Chu; Zeanah, Paula L.; Olivier, Dianne F.; Bergeron, Megan A.; Liu, Cindy H.
Abstract: The urgent closures of campuses nationwide due to the COVID-19 pandemic have presented unforeseen challenges to college students, who already showed concerning rates of mental health conditions and suicidality. Among US college students, more than one in five are parents raising young children. Student-parents are faced with compounding struggles that substantially intersect with those of minority students, students from low-income backgrounds, and first-generation students. However, the challenges and unique needs of student-parents have not been sufficiently recognized by the college administrations. As higher education grapples with supporting students to navigate through the pandemic, reaching out to student-parents and prioritizing their needs is indispensable to assure their continued engagement and completion of studies. The authors offer recommendations for college administrations to help alleviate strains in student-parents amid the crisis and promote strengths and resilience in the short term and beyond.